Budaya Organisasi, Motivasi, dan Pelatihan Terhadap Kinerja Karyawan: Peran Kompensasi Sebagai Moderator - Muhammad Rifqi; Rinda Asytuti (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
This study aims to determine the effect of organizational culture, motivation, and training on employee performance with compensation as a moderating variable. The population in this study was all BNI Syariah Pekalongan Branch employees, as many as 50 people. Data collection techniques using a questionnaire. Data were analyzed using moderation regression analysis with the interaction test method. The results of this study indicate that organizational culture, motivation, and training partially have a positive and significant effect on employee performance; compensation does not moderate the effect of organizational culture on employee performance; compensation moderates the influence of motivation on employee performance; and compensation moderates the effect of training on employee performance.